Does Technology Adoption Mediate the Determinant Factor of MSMEs Competitive Advantage? - Bakhtiar Abbas; Abdul Hakim; Muhammad Faried Pratama (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
This study explores the effect of human resource competence, entrepreneurial orientation, and also social capital on MSMEs competitive advantages mediated by technology adoption. This study employed a quantitative approach, utilizing a survey method to collect data from respondents. MSME actors in Kendari, Southeast Sulawesi were being population in this research. Purposive sampling was used to choose the 150 MSME actors that made up the research sample. This research uses data analysis with the Partial Least Square (PLS) approach assisted by SmartPLS. The analysis results indicate that human resource competence, entrepreneurial orientation, and also social capital significantly and positively affect MSMEs competitiveness. However, technology adoption does not significantly affect MSMEs competitive advantage in Kendari, Southeast Sulawesi. Technology adoption is able to strengthen mediate the effect of human resource competence and entrepreneurial orientation on MSMEs competitiveness. However, it does not mediate the relationship between social capital and MSMEs competitiveness. This research contributes to the theoretical framework of MSMEs competitive advantage by integrating technologies challenges to the MSMEs sector. The study provides practical insights for MSME emphasizing the need should be more informed with competence and strategic concerns.